2008
DOI: 10.1074/jbc.m709140200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Pro-matrix Metalloproteinase-9/Proteoglycan Heteromer with Gelatin and Collagen

Abstract: Previously we have shown that THP-1 cells synthesize matrix metalloproteinase-9 (MMP-9) where a fraction of the enzyme is strongly linked to a proteoglycan (PG) core protein. In the present work we show that these pro-MMP-9⅐PG heteromers have different biochemical properties compared with the monomeric form of pro-MMP-9. In these heteromers, the fibronectin II-like domain in the catalytic site of the enzyme is hidden, and the fibronectin II-like-mediated binding to gelatin and collagen is prevented. However, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 54 publications
2
44
0
3
Order By: Relevance
“…Upregulation of endothelin receptors results in remodeling of MMPs and downregulation of connexin-43 through a common pathway (Peng, et al 2010). These MMPs are termed “gelatinases” and are known to degrade basement membrane proteins (Ahmed, et al 2006, Malla, et al 2008). An upregulation in MMP mRNA expression was observed following treatment with DEHP.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of endothelin receptors results in remodeling of MMPs and downregulation of connexin-43 through a common pathway (Peng, et al 2010). These MMPs are termed “gelatinases” and are known to degrade basement membrane proteins (Ahmed, et al 2006, Malla, et al 2008). An upregulation in MMP mRNA expression was observed following treatment with DEHP.…”
Section: Discussionmentioning
confidence: 99%
“…This is not documented in dentin, but we cannot exclude that the cleavage of the heteromer by MMP-3 may release activated MMP-9. Even in very small amount MMP-9 may digest physiological targets [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that DMSO and Triton X-100 have different abilities to detach gelatinase complexes from gelatin-Sepharose columns (Malla et al 2008a). Therefore, DMSO was also used to extract gelatin-degrading enzymes in the present study.…”
Section: Different Extraction Protocolsmentioning
confidence: 99%
“…Gelatin Zymography SDS-PAGE substrate zymography was carried out as described previously (Malla et al 2008a) with gels (7.5 3 8.5 cm 3 0.75 mm) containing 0.1% (w/v) gelatin and 4% and 7.5% (w/v) polyacrylamide in the stacking and separating gels, respectively. Eight ml of extract was mixed with 2 ml of loading buffer (333 mm TrisHCl, pH 6.8, 10% SDS, 0.03% bromophenol blue, and 50% glycerol).…”
Section: Extraction Of Proteases From Tissuementioning
confidence: 99%